Smart CCTVs: Third Eye of Secure Cities - Muhammad Faizal Bin Abdul Rahman (2016)
Many cities around the world are exploring the use of Smart CCTVs as advances in Artificial Intelligence (AI) offer operational value for homeland security. However, cybersecurity and overreliance could impede the technology’s potential.